2015
DOI: 10.1159/000437228
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Motor and Non-Motor Features in Medication-Naïve Parkinsonism

Abstract: Background: Parkinsonism is defined by motor features (tremor, bradykinesia, rigidity, and postural instability). Accompanying non-motor features (e.g. cognitive, autonomic, sleep disturbances) are underrecognized and undertreated. We hypothesized that clinical patterns occurring in early, medication-naïve Parkinsonism are distinguished by features such as tremor, sleep, autonomic, and cognitive dysfunction. Methods: Clinical and neuroimaging data were obtained in the Parkinson's Progression Marker Initiative.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 27 publications
1
1
1
Order By: Relevance
“…In contrast to the lack of clusters in our motor FND group of patients, previous high-quality studies using the same methodology (gap statistics) reported homogeneous clusters including drug-naive parkinsonism (Jain, Park, & Comer, 2015), comorbidities associated with obesity (Reategui, Ratte, Bautista-Valarezo, & Duque, 2019), breast cancer progression data (Alexe, Dalgin, Ganesan, Delisi, & Bhanot, 2007). However, most cluster analysis studies in neurological conditions with motor symptoms such as Parkinson's disease (Ba, Obaid, Wieler, Camicioli, & Martin, 2016; Mu et al, 2017; Yang, Kim, Yun, Kim, & Jeon, 2014) or fibromyalgia (Yim et al, 2017) suffered from important methodological problems which could have led to false-positive cluster identification.…”
Section: Cluster Analysiscontrasting
confidence: 77%
“…In contrast to the lack of clusters in our motor FND group of patients, previous high-quality studies using the same methodology (gap statistics) reported homogeneous clusters including drug-naive parkinsonism (Jain, Park, & Comer, 2015), comorbidities associated with obesity (Reategui, Ratte, Bautista-Valarezo, & Duque, 2019), breast cancer progression data (Alexe, Dalgin, Ganesan, Delisi, & Bhanot, 2007). However, most cluster analysis studies in neurological conditions with motor symptoms such as Parkinson's disease (Ba, Obaid, Wieler, Camicioli, & Martin, 2016; Mu et al, 2017; Yang, Kim, Yun, Kim, & Jeon, 2014) or fibromyalgia (Yim et al, 2017) suffered from important methodological problems which could have led to false-positive cluster identification.…”
Section: Cluster Analysiscontrasting
confidence: 77%
“…Both features also significantly differed between early PD and SWEDD but not early PD and controls (see Tables 1, 2). These findings, in concert with other PPMI data research (40,89), warrant further investigation. Is the difference in years of education, fewer years of education in SWEDD, just specific to the particular SWEDD cohort used?…”
Section: Discussionsupporting
confidence: 57%
“…Given his interests, it is not surprising that Samay wrote extensively about nonmotor and autonomic features of PD. Indeed, he performed both original clinical laboratory‐based research and epidemiological studies of these aspects of the disease, and he also wrote well‐cited reviews . In 2012, together with David Goldstein, Samay guest edited a special issue of Neurobiology of Disease that was dedicated to nonmotor aspects of PD.…”
mentioning
confidence: 99%